PERUBAHAN KECEMASAN PASIEN PRA OPERASI SECTIO CAESAREA DENGAN PEMBERIAN KOMUNIKASITERAPEUTIK METODE HELPING RELATIONSHIP DI RUMAH SAKIT BINA SEHAT TAHUN 2018 - Sheila sela Setianing; I Gusti Ayu Karnasih; Ratna Suparwati; Yuniasih Purwaningrum (Jurnal Pendidikan Kesehatan, 2019)
Anxiety can be experienced by a person on the face of sugery, as well as mother who will undergo section caesaria surgery. Anxiety can increase blood preasure and the baby heart rate increases, so that anesthesia procedures can be delayed and can also impact on the prosess of sugery performed. One way to reduce anxiety is giving therapeutic communication. The purpose of this study to determined the decrease on the level of anxiety in mothers who will undergo section caesaria surgery, before and after done giving therapeutic communication.The search design One group pre test and post test. The population of this study were all mothers who would undergo section caesaria surgery electievy with 32 mothers in Bina Sehat Hospital. The sampling by technical Accidental Sampling. The result of previous research done giving therapeutic communication, which experienced mild anxiety as much 9,4 percent moderate anxiety as much 40,6 percent and severe anxiety 50 percent, where as after therapeutic communication method helping relationship done, who does not experience anxiety as much 3,1 percent, mild anxiety 46,9 percent, moderate anxiety 43,7 percent and severe anxiety 6,3 percent. Accoding tho wiloxon sign test, alpha is smaller than 0,05 get resuth Z count is greater than Z table. A mothers anxiety during surgery can be redused by giving therapeutic because there is emphaty, honesty, openness and positive attitude that midwive have in order mother to remainclam comfortable while undergo surgery